Empathic and peacebuilding gestures: an analysis of greeting gestures across cultures - Puppel, Joanna; Rozpendowska, Alicja (Scripta Neophilologica Posnaniensia, 2021)
Communication process allows people to receive and send messages through verbal and nonverbal resources which play an important role in healthy interpersonal acts. While verbal communication has been the subject of many studies, the present study aims to focus mainly on the nonverbal aspect that is greeting gestures. In this article we shall analyze which greeting gesture, that is widely used across different cultures may evoke a feeling of empathy and thus build peaceful interactions so needed in human communication nowadays.